Industrial training report: Sam Meerkat Sdn Bhd - Norzaini, Nur Atikah (Universiti Teknologi MARA, Perlis, 2024)
Internships provide students with valuable learning opportunities to develop and gain insight into the professional workplace. Furthermore, internships allow students to put into practice the concepts and theories they have studied in university within real-world scenarios. My internship program will begin on March 4, 2024, and end on August 9, 2024, spanning 24 weeks. I have been accepted by Sam Meerkat company for an internship in the Administration department. I have been assigned to undergo this internship to gain experience and enhance my skills using what I have learned during my university studies to help the company operate more effectively. Throughout this training process, I have received guidance and tasks from my supervisor, Ms. Malisa Binti Matzen. This report is created to analyze how Sam Meerkat company operates. The report includes identifying the company's vision, mission, SWOT analysis, and PESTEL analysis. Therefore, several recommendations have been provided to help the company improve. One of the important things I have learned during my internship in this company as an admin is that admin tasks are crucial in ensuring that every item issued complies with the SOPs established by the company. It is also important to ensure that all company data and information are securely stored, including preserving important documents in both physical and digital formats to prevent any undesirable incidents for the company. I have also learned how to efficiently create Purchase Orders (POs) and invoices. POs and invoices must be made accurately and neatly to ensure that customers receive the desired goods, maintaining the company's reputation and gaining trust and confidence from customers to continue doing business with the company. Overall, I have learned a lot during my internship at Sam Meerkat. I have successfully improved my skills and gained various interesting experiences. I am confident that all the experiences and skills I have gained in this company will help me in the future.